2016
DOI: 10.1128/jcm.02497-15
|View full text |Cite
|
Sign up to set email alerts
|

How Many Samples and How Many Culture Media To Diagnose a Prosthetic Joint Infection: a Clinical and Microbiological Prospective Multicenter Study

Abstract: h Although numerous perioperative samples and culture media are required to diagnose prosthetic joint infection (PJI), their exact number and types have not yet been definitely determined with a high level of proof. We conducted a prospective multicenter study to determine the minimal number of samples and culture media required for accurate diagnosis of PJI. Over a 2-year period, consecutive patients with clinical signs suggesting PJI were included, with five perioperative samples per patient. The bacteriolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
66
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(81 citation statements)
references
References 23 publications
(39 reference statements)
4
66
1
2
Order By: Relevance
“…Results of this study are similar to those of the recently published study by Bémer et al (12) assessing the number of perioperative specimens, including periprosthetic tissue, bone, and joint fluid samples, required for the accurate diagnosis of PJI. This prospective cohort study involved 215 patients with confirmed PJI according to modified IDSA criteria (3,12).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Results of this study are similar to those of the recently published study by Bémer et al (12) assessing the number of perioperative specimens, including periprosthetic tissue, bone, and joint fluid samples, required for the accurate diagnosis of PJI. This prospective cohort study involved 215 patients with confirmed PJI according to modified IDSA criteria (3,12).…”
Section: Discussionsupporting
confidence: 81%
“…Also at variance is that Schaedler broth was used for anaerobic culture and that patients without PJI were not included. In addition, the microbiological criteria used by Bémer et al and in our study differed; in our study, a culture result was considered positive only if the same microorganism was isolated in two or more specimens with no reference to organism type or virulence (4,12).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Ameliyat sırasında kültür örneği alınırken, en az üç adet olması-na özen gösterilmelidir; hatta en az 5-6 örnek alınma-sını telkin eden çalışma sonuçları da vardır. [17] Son yıllarda, total protez enfeksiyonlarının tanısında immünofloresan mikroskopi ve PCR (polimeraz zincir reaksiyonu) gibi moleküler yöntemlerin kullanılmasıyla ilgili araştırmalar yapılmaktadır. [18,19] Yakın zamanda, Amerikan Enfeksiyon Derneği'nin yıllık toplantısında bildirilen bir çalışmada, PCR'nin kültüre bir üstünlüğü olmadığı bildirilmiştir.…”
unclassified